Role of Susceptibility Weighted Imaging (SWI) in the Diagnosis of Abdominal Wall Endometriosis - (:unkn) unknown (My University, 2016)
Amaç: Pelvis dışı endometriozisin bir alt tipi olan abdominal duvar endometriozisi nadir görülmekte olup olgular özellikle menstrüasyonla şiddetlenen ağrılı kitle ile başvururlar. Kitlenin deığerlendirilmesinde ultrasonografi ve MRG önerilen tanı yöntemleridir. Granülasyon zemininde kalsifikasyonun kronik kan ürünlerinden ayırdedilemediği durumlarda tanı biyopsi ile konulur. Suseptibilite ağırlıklı görüntüleme (SAG), komşu dokular arasındaki manyetik duyarlılık farklarını imaj oluşturmakta kullanan göreceli yeni bir tekniktir. Kan ürünlerine duyarlılığı konvansiyonel MRG'ye göre daha yüksek olan SAG sekansı esas olarak nöroradyoloji alanında kullanılmakta ancak son çalışmalarda batın görüntülemede ek tanısal bilgi sağladığı gösterilmektedir. Bu yazıda SAG'nin abdominal duvar endometriozisi lezyonlarında tanısal yararlılığını göstermeyi amaçlıyoruz.Olgu: Beş yıl önce sezaryen ile doğum öyküsü olan 29 yaşındaki kadın hasta sezaryen skarı süperior kesiminde, orta hattın solunda ağrılı ve zamanla büyüyen kitle şikayeti ile başvurdu. Yapılan ultrasonografide rektus fasyası altında heterojen hipoekoik solid lezyon tespit edildi. MRG de rektus abdominis kasına bitişik yerleşimli düzensiz şekilli lezyon içerisinde kronik kan ürünleri ile kalsifikasyon ayırımının net yapılamadığı kontrast tutan heterojen kitle görüldü. SAG sekansta sinyal void olarak izlenen odakların faz imajlarda hiperintens görülmesi kalsifikasyon olasılığını ekarte etmiş, endometriozis tanısını desteklemiştir.Sonuç: Abdominal duvar endometriozisi şüpheli olgularda MR tetkikine eklenen SAG sekansı menstürasyon ve menstürasyon dışı dönemlerde değişik fazlardaki kan ürünlerini gösterebilmesinin yanında, faz imajların katkısıyla kalsifikasyon olasılığının ortadan kaldırılmasında önemli bir rol oynayarak tanıyı kolaylaştırmaktadır.

Objective: Abdominal wall endometriosis is a rare subtype of extra-pelvic endometriosis; and the patients present with a painful abdominal mass that is particularly aggravated by menstruation. Ultrasound and MRI are the recommended diagnostic tools for the evaluation of the mass lesions. Biopsy is performed when calcifications in the granulation tissue cannot be differentiated from chronic blood products. Susceptibility weighted imaging (SWI) is a relatively new MR technique where the image contrast is mainly based on magnetic susceptibility differences. SWI has higher sensitivity to blood products compared to conventional MRI sequences. Although it has been mostly used in neuroimaging studies, recent studies have shown that it provides additional diagnostic information abdominal imaging. In this article, we aim to demonstrate the diagnostic utility of SWI for lesions of abdominal wall endometriosis.Case: A 29-year-old woman with a history of Caesarean-section delivery five years ago presented with a cyclic pain and slowly growing abdominal mass located superior to the Caesarean incision scar on the left side of the midline. A heterogeneous hypoechoic solid mass was detected ultrasonographically underneath the fascia of rectus muscle. On MRI, a solid heterogeneous enhancing lesion located anterior to the rectus muscle was seen in which blood products and calcifications could not be differentiated by their signal intensities. On SWI sequence, signal voids within the lesion on magnitude images were hyperintense on phase images and this excluded calcifications endorsing endometriosis as diagnosis. Conclusion: SWI imaging with its high sensitivity to blood products, contributes to the diagnosis of abdominal wall endometriosis by depicting different phases of hemorrhage during menstruation and non-menstruating days. Another advantage of SWI is the ability to differentiate between blood products and calcification which provides additional value to improve diagnostic ability of pelvic MRI.
Suseptibilite ağırlıklı manyetik rezonans görüntüleme sekansının abdominal duvar endometriozisi tanısına katkısı
Keywords: Cerrahi